2015
DOI: 10.7883/yoken.jjid.2014.288
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Yellow Fever Virus in Selected Health Facilities in Western Kenya from 2010 to 2012

Abstract: SUMMARY: Yellow fever (YF), which is caused by a mosquito-borne virus, is an important viral hemorrhagic fever endemic in equatorial Africa and South America. Yellow fever virus (YFV) is the prototype of the family Flaviviridae and genus Flavivirus. The aim of this study was to determine the seroprevalence of YFV in selected health facilities in Western Kenya during the period 2010-2012. A total of 469 serum samples from febrile patients were tested for YFV antibodies using in-house IgM-capture ELISA, in-house… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 17 publications
1
13
1
Order By: Relevance
“…However, the observed overall sero-prevalence (49.5%) of IgG antibody against YFV was low compared to the results of other sero-prevalence studies conducted in YF vaccinated populations in Sudan [32], Brazil [33] and other country [34]. On the other hand, the sero-prevalence against YFV in our study was still higher than the national pooled sero-prevalence of Ethiopia [35] and Western Kenya [19]. These geographic based https://doi.org/10.1371/journal.pntd.0008549.g003…”
Section: Plos Neglected Tropical Diseasescontrasting
confidence: 95%
See 1 more Smart Citation
“…However, the observed overall sero-prevalence (49.5%) of IgG antibody against YFV was low compared to the results of other sero-prevalence studies conducted in YF vaccinated populations in Sudan [32], Brazil [33] and other country [34]. On the other hand, the sero-prevalence against YFV in our study was still higher than the national pooled sero-prevalence of Ethiopia [35] and Western Kenya [19]. These geographic based https://doi.org/10.1371/journal.pntd.0008549.g003…”
Section: Plos Neglected Tropical Diseasescontrasting
confidence: 95%
“…CHIK outbreaks have been reported from many African countries including Uganda [ 13 ], Kenya [ 14 – 16 ], Sudan [ 17 ] and Tanzania [ 18 ]. Despite the proximity of Ethiopia to these countries, and migration of people across the border between Ethiopia and contingent countries as well as the existence of the potential mosquito vectors ( Aedes bromeliae and Aedes aegypti ) responsible for transmitting CHIKV in the study area [ 9 ], and the repeatedly occurrence of CHIK outbreaks in Kenya [ 14 – 16 , 19 , 20 ], either health facility or community-based survey of CHIKV infection has not been conducted in the present study area.…”
Section: Introductionmentioning
confidence: 99%
“…We recorded lower YFV seroprevalence than previously reported in children by Kwallah et al (2015), similar to the rates reported in children (Sutherland et al, 2011) and in adults in Western Kenya (Mease et al, 2011;Kwallah et al, 2015) and higher than an earlier study (Geser et al, 1970). The YFV seroprevalence of 0.5% by PRNT in the present study is higher than that in one earlier study (Geser et al, 1970), but lower than that in another (Kwallah et al, 2015). The rates reported in current studies may mean that YFV is spreading locally.…”
Section: Discussionsupporting
confidence: 89%
“…The differences seen in these studies may be attributed to the different detection methods used at the time (Geser et al, 1970;Vu et al, 2017), different time periods (Geser et al,1970;Vu et al, 2017), different climatic conditions or geographic regions (Kwallah et al, 2015;Mease et al, 2011;Vu et al, 2017), or different environmental, vector, andhost dynamics (Grossi-Soyster et al, 2017;Ngugi et al, 2017;Ndenga et al, 2017;Mwongula et al, 2013;Awando et al, 2013;Kwallah et al, 2015;Ochieng et al, 2015;Vu et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…9 Recent studies conducted in Western Kenya show that Arboviruses are circulating. [10][11][12] ONNV was initially isolated in Northern Uganda from anopheline mosquitoes and human serum during a 1959 epidemic. 13 During 1959-1962, there was an outbreak of ONNV fever that began in northern Uganda and involved an estimated 2 million people in Kenya, Tanzania, and Uganda.…”
mentioning
confidence: 99%